Formatos de televisión y derechos de autor: una mirada desde la jurisprudencia nacional y comparada - Montezuma Panez, Oscar (2015)
TV formats are one of the most used mechanisms in the audiovisual industry. Their protection by copyright is a subject of academic debate which reflects in the diverse international and national jurisprudence on the matter. This article aims to give a brief review of some theoretical aspects regarding the type of protection provided by copyright to audiovisual productions, providinga case law approach on recent Peruvian and international jurisprudence.